Analisis Kebutuhan Pengembangan Modul Pembelajaran Fisika SMA Berbasis Pendekatan STEM - Marta, Yonira Mike Vindi; Ramli, Ramli (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
The application of the STEM approach must be supported by the existence of teaching materials that are in accordance with the characteristics and needs of students. One of the teaching materials that can support independent learning is modules. However, there are still modules that have not fully facilitated the application of STEM in physics learning. Modules that have not fully facilitated the application of the STEM approach in learning physics. This study aims to analyze the needs of module based on the STEM approach in learning physics. This research is a descriptive study conducted through observations in Senior High Schools (SMA N 9 Padang) with the research sample being students of class XI. Analysis of module needs based on the STEM approach, including student analysis, analysis of learning activities, analysis of graduate competency standards, and assessment analysis. The instruments in this study were questionnaires and interview sheets. The results showed that the mean score of the students was 71.42, the analysis of learning activities obtained an average value of 92.84, the standard analysis of the competence of graduates obtained an average value of 91.84 and the assessment analysis obtained an average value of 100. Therefore, it is necessary to develop physics teaching materials in the form of modules based on the STEM approach.